Assessment of hepatocellular carcinoma risk based on peg-interferon plus ribavirin treatment experience in this new era of highly effective oral antiviral drugs. Issue 1 (January 2017) - Lee, Seung Ho; Jin, Young-Joo; Shin, Jun Young; Lee, Jin-Woo
Abstract : Abstract: In this new era of highly effective oral antiviral drugs for chronic hepatitis C virus (HCV), indications for antiviral treatment may be extendable. This study undertaken to identify suitable candidates for peg-interferon plus ribavirin (PEG-IFN/RBV) treatment by evaluating hepatocellular carcinoma (HCC) risk in patients with chronic HCV treated or not with PEG-IFN/RBV. This large-scale retrospective study was conducted on 1176 patients with chronic HCV without a history of HCC (treatment group [n = 489] and no-treatment group [n = 687]). In the treatment group, patients treated with PEG-IFN/RBV were dichotomized based on the achievement of sustained virologic response (SVR) into SVR (+) and SVR (−) groups. Median follow-up for all study subjects was 31 months (range 6–144 months). Three-year cumulative HCC development rates in the SVR (+) (1.1%) and SVR (−) (8.6%) subgroups were significantly lower than in the no-treatment group (13.5%) ( P < 0.01 and P < 0.01, respectively). In all study subjects, presence of cirrhosis (hazard ratio [HR], 9.92, P < 0.01), age (HR 1.03, P < 0.01), SVR (−) (HR 7.02, P < 0.01), and no-treatment (HR 6.76, P < 0.01) were found to be independent risk factors of HCC development. In the treatment group, age, the presence of cirrhosis, and SVR (−) were predictors of HCC development. In the no-treatment group, age, male, and the presence of cirrhosis were independent predictors for HCC development. HCC risk increased in patients with chronic HCV with older age, cirrhosis, SVR (−) after PEG-IFN/RBV treatment, and no PEG-IFN/RBV treatment. Active antiviral therapy based on highly effective oral drugs needs to be considered in these patients.